Proceedings of the 23rd International Conference on World Wide Web 2014
DOI: 10.1145/2567948.2578835
|View full text |Cite
|
Sign up to set email alerts
|

Community-based crowdsourcing

Abstract: This paper is focused on community-based crowdsourcing applications, i.e. the ability of spawning crowdsourcing tasks upon multiple communities of performers, thus leveraging the peculiar characteristics and capabilities of the community members. We show that dynamic adaptation of crowdsourcing campaigns to community behaviour is particularly relevant. We demonstrate that this approach can be very effective for obtaining answers from communities, with very different size, precision, delay and cost, by exploiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…We focus on eliciting visual feedback from unpaid community members of an operational website. As such, our approach uses community-based crowdsourcing [6] or community sourcing [20]. The feedback requester in our system is the web designer or the web developer.…”
Section: Design Feedback From the Non-expert Crowdmentioning
confidence: 99%
“…We focus on eliciting visual feedback from unpaid community members of an operational website. As such, our approach uses community-based crowdsourcing [6] or community sourcing [20]. The feedback requester in our system is the web designer or the web developer.…”
Section: Design Feedback From the Non-expert Crowdmentioning
confidence: 99%
“…[15] reported that crowd-sourcing can be expensive or unreliable as it requires no or little expertise from participants and no supervision of participants [16]. Similarly, [17][18][19][20] contend that crowd-sourcing is a powerful mechanism for outsourcing tasks which are traditionally performed by a specialist or small group of experts for a large group of community. Crowdsourcing has long been recognized as a potential of solving problems that require humans (i.e., where technology either cannot complete the task or where people can do it better).…”
Section: Obstacle Annotation and Crowdsourcingmentioning
confidence: 99%
“…al. [32] in the form of a control-mart for dynamic adaptations during task executions. recognized as services.KM-P has different tasks, which a knowledge space tries to execute.…”
Section: Findings and Challengesmentioning
confidence: 99%